STRATEGI INVESTASI TEKNOLOGI DAN PENDEKATAN INOVATIF JEPANG DALAM MENINGKATKAN KETAHANAN DAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA: STRATEGI INVESTASI TEKNOLOGI DAN PENDEKATAN INOVATIF JEPANG DALAM MENINGKATKAN KETAHANAN DAN PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Ryan Fadhlur Fajri; Syamsul Maarif; Yuli Subiakto; Pujo Widodo; Kusuma (CV. AFDIFAL MAJU BERKAH, 2023)
Technology and innovation play a crucial role in enhancing a country's resilience and sustainable development. Indonesia as a developing country has great potential to improve resilience and sustainable development through technology development and innovation. By adopting some of the technology investment strategies and innovative approaches that have been successfully implemented by Japan, Indonesia can accelerate progress and achieve sustainable development goals and simultaneously improve resilience in the face of disastersThis research uses descriptive qualitative methods through Focus Group Discussion (FGD) and literature study. As for the selection of resource persons, the technique was carried out by purposive sampling in the activities of the Study Abroad (KKLN) of the Disaster Management Study Program of the Republic of Indonesia Defence University in 2023. By adopting several initiatives that have been successfully implemented by Japan, Indonesia can accelerate progress and achieve sustainable development goals. The implementation of Japan''s technology investment strategy in Indonesia can assist in the development and improvement of advanced early warning systems, which can provide quick and accurate information to the public about impending disaster threats.